Rola i pozycja społeczna kobiet we wczesnej epoce żelaza przez pryzmat zmian w rytuałach pogrzebowych – na przykładzie Wielkopolski - Żychlińska, Justyna (Folia Praehistorica Posnaniensia, 2016)
This paper proposes that the beginning of the Early Iron Age saw the change of the social role and status of women. The study was based on the analysis of dozens of graves attributable to the Lusatian Culture, which spanned the Bronze and Early Iron Ages. Included in the analyses were only graves of individuals, whose sex and age could be anthropologically determined. The hypothesis is justified on the basis of the socio-symbolic dimension of weaving and pottery.